2018
DOI: 10.1097/md.0000000000013582
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial calcification found in Epstein–Barr viral myocarditis and rhabdomyolysis

Abstract: Rationale:The Epstein–Barr (EB) virus has rarely been reported as a cause of fulminant myocarditis. To our knowledge, the present case is the first report on myocardial calcification in EB viral myocarditis and rhabdomyolysis.Patient concerns:A 17-year-old man was admitted to the department with fever, chest tightness, and tachypnea that had been present for 2 days.Diagnoses:The initial investigation showed elevated liver enzyme levels, creatine kinase levels, creatine kinase isoenzyme levels, and elevated ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Sui et al reported a 17‐year‐old male with fulminant EBV myocarditis and rhabdomyolysis who developed extensive calcification of left ventricular walls. Despite the severe progression of the disease, he survived eventually with favorable follow‐up evaluations 21 . Watanabe et al described acute EBV myocarditis in a young female, complicated with malignant ventricular arrhythmias and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Sui et al reported a 17‐year‐old male with fulminant EBV myocarditis and rhabdomyolysis who developed extensive calcification of left ventricular walls. Despite the severe progression of the disease, he survived eventually with favorable follow‐up evaluations 21 . Watanabe et al described acute EBV myocarditis in a young female, complicated with malignant ventricular arrhythmias and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is a symptom and sign of cardiac dysfunction. Undoubtedly, all EBV-related organic diseases of the heart, including myocarditis, CAI, pericardial effusion, and cardiac valvulopathies, could lead to heart failure ( 14 , 17 , 31 , 32 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…In terms of sex, there were 28 male ( 7 , 12 , 16 , 18 , 20 , 23 , 25 , 27 , 28 , 30 – 34 ) and 26 female patients ( 6 , 8 , 9 , 13 , 15 , 17 , 19 , 21 , 22 , 24 , 26 – 29 , 31 , 35 ). Regarding the diagnosis of EBV infection, 23 (42.6%) were diagnosed with AEBV ( 6 , 13 15 , 17 , 18 , 25 , 27 , 32 ), 20 (37.0%) with CAEBV ( 7 , 8 , 16 , 19 22 , 28 – 31 , 34 ), 6 (11.1%) had a complication of CAEBV and HLH ( 12 , 24 , 28 , 31 ), 4 (7.4%) had a diagnosis of EBV-HLH ( 9 , 23 , 33 , 35 ), and 1 (1.9%) had reactivated EBV ( 26 ).…”
Section: Different Cardiovascular Manifestations and Diagnosis In Pat...mentioning
confidence: 99%
See 2 more Smart Citations